Plan Estratégico para la Ferretería Hiperconstrucción de la Ciudad de Loja para el periodo 2016 - 2021 - Villa Granda, Diego Vicente (2017)
Strategic planning has become vital within organizations, so a good plan is one that manages to produce an excellent interpretation of the situation; And, consequently, allows the chosen route to be precise enough to prevent the challenges facing us in practice. So that the current research work was developed with the objective of supporting the development of the "HIPERCONSTRUCCIÓN" hardware store, to renew the activities that it performs and to overcome the different deficiencies existing in the hardware store, which were identified through the process Where the dialectical method and research techniques were used to obtain the necessary information and to establish the real situation of how it is found. In the development of the research, the external analysis was carried out, based on Porter's five forces, as well as the political, economic, social and technological (PEST) analysis, thus establishing the opportunities and threats faced by the company. In the internal analysis it was done, analyzing the different departments such as: Administration, Marketing, Operations and logistics, Finance and accounting, Human resources, information and communications systems and technology, thus determining the strengths and weaknesses of the 5 company; With these results, the Internal Factor Evaluation Matrix (MEFI) was elaborated. The results of the matrix of evaluation of external factors reached a value of 2.58, and the result of the matrix of internal factors of 2.25, which means that the company is moderately stable, for that reason considers the need To propose strategies to counter the threats and weaknesses of the hardware store. Once the internal and external analyzes were carried out, the High Impact Matrix SWOT was elaborated to establish the strategic objectives that the company must carry out in order to balance the different variables that are presented. Once the previous factors were fulfilled, the proposal for the long-term Plan was executed. Based on this, the first year's annual operational plan was elaborated to meet the strategic objectives, which included strategies, tactics, budgets and responsible. From this table it is concluded that the hardware does not have a promotion plan that allows it to attract customers, with trained personnel that differentiates from the competition.